Galactic cosmic ray effects on iron and nickel isotopes in iron meteorites - Cook, David L. (2021)
We present model calculations for cosmogenic production rates in order to quantify the potential effects of spallation and neutron capture reactions on Fe and Ni isotopes in iron meteorites. We aim to determine whether the magnitude of any cosmogenic effects on the isotopic ratios of Fe and/or Ni may hinder the search for nucleosynthetic variations in these elements or in the application of the 60Fe‐60Ni chronometer. The model shows that neutron capture reactions are the dominant source of shifts in Fe and Ni isotopic ratios and that spallation reactions are mostly negligible. The effects on 60Ni are sensitive to the Co/Ni ratio in the metal. The total galactic cosmic ray (GCR) effects on 60Ni and 64Ni can be minimized through the choice of normalizing isotopes (61Ni/58Ni versus 62Ni/58Ni). In nearly all cases, the GCR effects (neutron capture and/or spallation) on Fe and Ni isotopic ratios are smaller than the current analytical resolution of the isotopic measurements. The model predictions are compared to the Fe and Ni isotopic compositions measured in a suite of six group IAB irons with a range of cosmic ray exposure histories. The experimental data are in good agreement with the model results. The minimal effects of GCRs on Fe and Ni isotopes should not hamper the search for nucleosynthetic variations in these two elements or the application of the 60Fe‐60Ni chronometer in iron meteorites or chondrites.